The quality of Kopitiam physical environment: are patrons satisfied? / Safwana Nur Widad Safrin and Zurinawati Mohi - Safri, Safwana Nur Widad; Mohi, Zurinawati (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study examines the physical environment quality of Kopitiam patron satisfaction. Kopitiams shows a good image and reputation among other coffee shops in Malaysia. Kopitiam's owner should be concerned about the physical environment quality. An extensive literature review identified seven dimensions of Physical Environment Quality, i.e., Facility Aesthetics, Ambience, Interior Design, Layout and Design, Exterior Design, Authentic Design, and Cleanliness. One hundred eighty questionnaires were received. Data were obtained from a questionnaire distributed randomly to 180 respondents who experienced dining in selected Kopitiam. An online survey was also conducted to increase the positive response rate. The Google form link was sent to the patron who commented on the selected Kopitiam on Trivago.com. Data were analyzed using Exploratory Factor Analysis and Multiple Regression Analysis. As a result, the Authentic Design dimensions show a significant relationship towards Kopitiam patrons' satisfaction, followed by Cleanliness and Facility Aesthetic.